Study on regional characteristics of plant landscape in yao village of longsheng county - Li Hao Xin; Liang Zhen Ran (E3S Web of Conferences, 2021)
Taking the plant landscape of Baimian Yao Village and Huangluo Yao Village in the regional environment of Longsheng Autonomous County as the research object, combing and analyzing the status quo of their plant species and plant communities, and combining the folk culture and living area of the minority ethnic group in Guangxi—the Yao nationality,it summarizes the characteristics of plant landscape such as the application of native plant varieties, the level of plant vertical landscape space, and the combination of plant application and folk culture. In order to provide theoretical and practical guidance for the future plant landscape construction in this area.